2011
DOI: 10.1111/j.1349-7006.2010.01841.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral ingestion of Lentinula edodes mycelia extract inhibits B16 melanoma growth via mitigation of regulatory T cell‐mediated immunosuppression

Abstract: Mitigation of regulatory T cell-mediated immunosuppression is crucial for optimal in vivo anti-tumor immune responses. In this study, we examined the anti-tumor effect induced by oral ingestion of an immunomodulating diet comprised of Lentinula edodes mycelia (L.E.M.) extract. C57BL ⁄ 6 mice were inoculated subcutaneously in the footpad with B16 melanoma and fed L.E.M. extract. Ingestion of L.E.M. extract significantly inhibited tumor growth, and this in vivo anti-tumor effect was not observed in nude mice, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…cDNA was synthesized from sample RNA using ReverTra Ace RT PCR Kit (TOYOBO CO., LTD, Osaka, Japan). All real-time PCRs were performed with SYBR Green Premix Ex Taq (TaKaRa Bio Inc., Shiga, Japan) by the ABI 7500 Fast Real-Time PCR System (Applied Biosystems, Inc. Carlsbad, California, US) as described previously [22-25] using specific primers for individual genes. Fold changes of targeted genes of each sample were relatively quantified using threshold cycle (Ct) values and calculated using the ddCT method normalizing B-actin or 18S RNA values.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA was synthesized from sample RNA using ReverTra Ace RT PCR Kit (TOYOBO CO., LTD, Osaka, Japan). All real-time PCRs were performed with SYBR Green Premix Ex Taq (TaKaRa Bio Inc., Shiga, Japan) by the ABI 7500 Fast Real-Time PCR System (Applied Biosystems, Inc. Carlsbad, California, US) as described previously [22-25] using specific primers for individual genes. Fold changes of targeted genes of each sample were relatively quantified using threshold cycle (Ct) values and calculated using the ddCT method normalizing B-actin or 18S RNA values.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we recently reported that oral ingestion of L.E.M. extract can inhibit the growth of a subcutaneously established B16 melanoma in a T cell-dependent manner via mitigation of Treg-mediated immunosuppression (12). However, the question remains as to how an orally ingested L.E.M.…”
Section: Introductionmentioning
confidence: 98%
“…C26-inoculated mice, because we previously reported that oral ingestion of L.E.M. can mitigate Treg-mediated immunosuppression in mice bearing a subcutaneously established B16 melanoma (12). We therefore evaluated the percentage of Effects of ingestion of L.E.M.…”
Section: Tregs In the Mesenteric Lns And The Spleen Of The Icmentioning
confidence: 99%
“…A study in tumor-bearing mice reported that L.E.M. led to a decrease in tumor inducing regulatory T (Treg) cells and resolution of immunosuppression (Tanaka et al, 2011;. In addition, a study in patients receiving immunotherapy reported that L.E.M.…”
Section: Discussionmentioning
confidence: 99%